The prevalence and risk factors of low back pain in the eastern Black Sea region of Turkey - Çapkın, Erhan; Karkucak, Murat; Çakırbay, Haşim; Topbaş, Murat; Karaca, Adem; Köse, Muammer Muslim; Gökmen, Ferhat (IOS Press, 2015)
BACKGROUND: Low back pain (LBP) is a public health problem commonly seen in all societies. OBJECTIVE: The aim of this study was to determine the prevalence and specific risk factors of low back pain (LBP) in the central and outlying districts of the province of Trabzon, a Black Sea region of Turkey. METHOD: A random sample of 7897 (4006 men and 3789 women) adults was collected by using sampling techniques of stratification. In this study questionnaires were completed at face-to-face interviews with participants selected on the basis of place of residence, gender and age group. The used variables in this study were: use of cigarettes, status of marriage, level of education, and presence of chronic disease, the prevalence of lifetime LBP and of LBP in the preceding year. Chronic LBP was determined as being present for more than 6 weeks. RESULTS: The lifetime prevalence of LBP in the general population was determined at 62.1%. Prevalence in the preceding year was 46.1%, and that of LBP lasting more than six week was 18.1%. Lifetime prevalence of LBP, prevalence of LBP in the preceding year and prevalence of pain lasting more than six week were all statistically significantly higher in women (p < 0.001). Use of cigarettes, female gender, marriage, a low level of education and presence of chronic disease were identified as independent risk factors for LBP (p < 0.001). CONCLUSION: Lower back pain is a common public health problem. Recommendations were made for local health services to prevent LBP, including health education through combating chronic diseases, reducing cigarette consumption, improvement of working environments and life styles.
WOS: 000367258400020
PubMed ID: 25736952
Keywords: Low Back Pain; Prevalence; Turkey; Smoking; Life Style